Genetic mapping of a single nuclear locus determines the white flesh color in watermelon (Citrullus lanatus L.) - Yi, Licong; Zhou, Wei; Zhang, Yi; Chen, Zibiao; Wu, Na; Wang, Yunqiang; Dai, Zhaoyi (Frontiers in Plant Science, 2023)
Introduction Flesh color is an important trait in watermelon (Citrullus lanatus L.). Several flesh color genes have been identified in watermelon; however, the inheritance of and the molecular basis underlying the white flesh trait remain largely unknown. Methods In this study, segregation populations were constructed by crossing the canary yellow flesh line HSH-F with the white flesh line Sanbai to fine-map the white flesh gene in watermelon. Results Genetic analysis indicated that the white flesh trait is controlled by a single recessive locus, termed Clwf2. Map-based cloning delimited the Clwf2 locus to a 132.3-kb region on chromosome 6. The candidate region contains 13 putative genes, and four of them—Cla97C06G121860, Cla97C06G121880, Cla97C06G121890, and Cla97C06G121900—were significantly downregulated in the white flesh compared to the canary yellow flesh watermelon fruits. The Cla97C06G121890 gene, which encodes a tetratricopeptide repeat protein, showed almost no expression in the white flesh fruit before maturity, whereas it had a very high expression in the canary yellow flesh fruit at 18 days after pollination. Transmission electron microscopy revealed rounded and regularly shaped chromoplasts in both the canary yellow and white flesh fruits. Further quantitative real-time PCR analysis showed that the expression levels of several key plastid division genes and almost the entire carotenoid biosynthesis pathway genes were downregulated in the white flesh compared to the canary yellow flesh fruits. Discussion This study suggests that the proliferation inhibition of chromoplasts and downregulation of the CBP genes block the accumulation of carotenoids in watermelon and lead to white flesh. These findings advance and extend the understanding of the molecular mechanisms underlying white flesh trait formation and carotenoid biosynthesis in watermelon.